Evaluasi Pengawasan dan Pertanggungjawaban Biaya Pendidikan dalam Perspektif Manajemen Pendidikan - Eviyarman; Hamdi Abdul Karim (Lembaga Yasin AlSys, 2026)
Educational cost management is an important component of educational management because it determines the effectiveness, efficiency, transparency, and accountability of educational provision. However, the implementation of educational cost oversight and accountability still faces various constraints that may affect the quality of educational financial governance. This study aims to analyze the implementation of educational cost oversight and accountability from an educational management perspective and to identify the factors influencing its effectiveness. The study employed a library research method with a qualitative approach. Data were obtained by reviewing books, scientific journal articles, regulations, and documents relevant to educational financial management and were then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that the effectiveness of educational cost oversight is influenced by internal control systems, the competence of financial managers, stakeholder participation, and the use of information technology. Educational cost accountability is realized through the preparation of transparent and accurate financial reports that are accessible to interested parties. The application of transparency and accountability principles can increase public trust and promote the efficient use of educational budgets. This study confirms that strengthening financial oversight and accountability systems needs to be positioned as an integral part of good educational governance. These findings contribute to the development of educational financial management studies and provide practical implications for educational institutions in improving the quality of budgetary control, reporting, and responsible use.